PENGARUH KEPERCAYAAN, KEPUASAN DAN KOMITMEN ORGANISASI TERHADAP PERILAKU KARYAWAN - Tri Aji, Fajar; Vemberi, Yohannes (Kajian Ekonomi dan Bisnis, 2023)
This study aims to analyze the effect of trust, satisfaction and organizational commitment on employee behavior. The subject used in this research is PT.Sinar Utama Sejahtera Klaten. The data used in this study are primary and secondary data obtained from the field and company data. The sample in this study were 130 respondents, namely employees of PT. Sinar Utama Sejahtera Klaten. The analytical method used is quantitative analysis, namely analysis which includes: validity test, reliability test, classic assumption test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, hypothesis testing through t test, F test and the coefficient of determination . By using SPSS tool ver 22. The results of this study indicate that trust, satisfaction and organizational commitment partially and simultaneously influence the behavior of PT. Sinar Utama Sejahtera Klaten employees.   Keywords: The Effect of Trust, Satisfaction, and Organizational Commitment on Employee Behavior.